Личностный рост, становление, самоактуализация (самоосуществление) - Сальникова, Т. С. (ХНУРЕ, 2020)
Any successful person should always change and grow up as a personality. This is possible through the self-realization and personal growth. Personal growth is very important thing for successful people. It includes relationship with oneself, relationships with other people and self-realization. Personal growth is a global process of developing person’s mental world. Soft skills are an important part of working process; they help us to communicate with the team. If person changes like personality in better side, it helps him to become a leader. But the way to the leadership are very long and hard-working.
Keywords: философия; личностный рост